SECURITY OF CELLULAR COMMUNICATION SYSTEMS! - Abdugafur Hotamov; Shahlo Rasulova (Journals Park Publishing, 2023)
First generation cellular communication systems such as NMT, TACS and AMPS had little security capability and this resulted in significant levels of fraudulent activity that harms both subscribers and network operators. A number of incidents of great significance have highlighted the sensitivity of analog telephones to eavesdropping on radio lines. The GSM system has many security features that are designed to provide the subscriber and network operator with a greater level of protection against fraudulent activity.
Keywords: protection level, access network, identifier, security aspects, Internet banking.